2018
DOI: 10.3847/1538-4357/aac6d8
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle Observations of the Neon Abundance in the Sun-as-a-star

Abstract: Properties of the Sun's interior can be determined accurately from helioseismological measurements of solar oscillations. These measurements, however, are in conflict with photospheric elemental abundances derived using 3D hydrodynamic models of the solar atmosphere. This divergence of theory and helioseismology is known as the "solar modeling problem." One possible solution is that the photospheric neon abundance, which is deduced indirectly by combining the coronal Ne/O ratio with the photospheric O abundanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The FIP effect is reduced at lower temperatures (Laming et al 1995). Recent work of Brooks et al (2017Brooks et al ( , 2018 based on Sun-as-a-star spectra obtained by the Solar Dynamics Observatory (SDO) Extreme-Ultraviolet Variability Experiment (EVE) demonstrated that the variation of coronal composition is highly correlated with the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The FIP effect is reduced at lower temperatures (Laming et al 1995). Recent work of Brooks et al (2017Brooks et al ( , 2018 based on Sun-as-a-star spectra obtained by the Solar Dynamics Observatory (SDO) Extreme-Ultraviolet Variability Experiment (EVE) demonstrated that the variation of coronal composition is highly correlated with the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…For the Sun, there is some evidence that the cyclic variation results from changes in the low FIP elements, since a similar cyclic variation is not seen directly in the high FIP element Ne (Schmelz et al 2005;Del Zanna & Andretta 2011). On the contrary, the Ne/O abundance ratio appears to vary with the solar cycle in the solar corona and solar wind (Shearer et al 2014;Landi & Testa 2015;Brooks et al 2018), which could in principle be due to changes in the Ne abundance. Solarlike stars of a similar spectral type to the Sun may show cyclic variations, but it may be more difficult to detect on later spectral type stars -where the inverse FIP effect is seen.…”
mentioning
confidence: 99%
“…This result confirms the finding of McIntosh et al (2011), which found that the Fe/O ratio, another proxy for the FIP effect in the solar wind, also shows some degree of variability in the fast wind during the decay phase of the solar cycle from 2005 to 2009. Further remote sensing observations of the sun-as-a-star by Brooks et al (2017Brooks et al ( , 2018) also indicate that during the rising phase of the solar cycle (2010-2014) the FIP bias changes with time: their measurements mostly reflect the composition of the denser quiet Sun and active region plasmas where the reconnection-based slow wind likely comes from. Furthermore, despite the uncertainties in its measurement, the abundance of Ne seems to increase during solar minimum relative to all other elements, and the amount of increase seems to be lower at larger speeds.…”
Section: Relative Elemental Abundancesmentioning
confidence: 99%